Relation of Refraction Abnormalities and Nutritional Status With Learning Achievement In Covid-19 Pandemic Era - Seyum Indrakila; Soetrisno Soetrisno; Annang Giri Moelya; Hary Wahyu Nugroho; Hafi Nurinasari (Gaster, 2021)
Refraction abnormalities are the second most common cause of limited vision after cataracts and being a health problem around the world, including Indonesia. Vision is the main factor of information input and learning process. Vision ability develops optimally until the age of 9 years, delays in refraction correction can cause reduced ability to absorb learning material and further will have an impact on learning achievement. However in pandemic era, learning system is turn into online system. Another factor that affects it is nutritional status, a body state caused by a balanced nutrient intake and needs. This study aims to prove the theory of the effect of refractive errors, nutritional status, on learning achievement. A cross-sectional design that linked refractive errors (myopia, hypermetropia, astigmatism) and nutritional status to learning achievement in elementary school student. The sample consisted of 26 students in grades 3-6. The refractive spearman test with learning achievement got a significance value of 0.733(p>0.05), while nutritional status and learning achievement has a significance value of 0.679(p>0.05) which means there are no meaningful relationship in both variable with learning achievement. Multivariate analysis was not performed because of the bivariate analysis were not significant. There was no correlation between students’ refractive abnormality and nutritional status with their learning achievement in pandemic era.